2021
DOI: 10.1042/bsr20203231
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an autophagy-related gene signature predicting overall survival for hepatocellular carcinoma

Abstract: The poor prognosis of hepatocellular carcinoma (HCC) calls for the development of accurate prognostic models. The growing number of studies indicating a correlation between autophagy activity and HCC indicates there is a commitment to finding solutions for the prognosis of HCC from the perspective of autophagy. We used a cohort in The Cancer Genome Atlas (TCGA) to evaluate the expression of autophagy-related genes in 371 HCC samples using univariate Cox and lasso Cox regression analysis, and the prognostic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In order to maintain the stability of the intracellular environment, autophagy involves degradation of damaged organelles or expired proteins to provide additional energy [23] [24]. Although autophagy is a normal physiological lysosome-dependent cellular self-degradation process [25], overactive autophagy may promote secondary cell death[26], as well as lead to excessive protein degradation and autophagic cell death [ 27 ] . According to previous studies[28] [29], ischemia can upregulate the autophagy activity in motor neurons, which might result in neuronal death after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…In order to maintain the stability of the intracellular environment, autophagy involves degradation of damaged organelles or expired proteins to provide additional energy [23] [24]. Although autophagy is a normal physiological lysosome-dependent cellular self-degradation process [25], overactive autophagy may promote secondary cell death[26], as well as lead to excessive protein degradation and autophagic cell death [ 27 ] . According to previous studies[28] [29], ischemia can upregulate the autophagy activity in motor neurons, which might result in neuronal death after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have revealed the role of gene signature in predicting survival outcomes of HCC. Specifically, Wang et al ( 2020 ) identified a five immune-related gene signature, Liu et al ( 2020 ) developed a four-gene metabolic signature, and Xu et al ( 2021 ) generated an eight autophagy-related gene signature. However, our eight-HRG signature had a higher AUC in survival prediction than the above three gene signatures.…”
Section: Discussionmentioning
confidence: 99%
“…1 Hepatocellular carcinoma (HCC) accounts for 85% of cases of primary liver cancer. 2 Serum alpha-fetoprotein (AFP) is recommended as an HCC-specific biomarker and is widely used in diagnosis and prognosis in HCC. 3,4 The positive rate of AFP is 41%-65% in patients with HCC, 5 and it is commonly assumed that serum AFP level has no diagnostic or prognostic role in AFP-negative HCC patients.…”
Section: Introductionmentioning
confidence: 99%